Pengaruh Penggunaan Media Video untuk Meningkatkan Hasil Belajar Siswa pada Pembelajaran IPS di SD - Alvira Oktavia Safitri; Puji Ayu Handayani; Tin Rustini (Departement of Mathematics Education, 2022)
The writing of the results of the research aims to find out how the influence of the use of video media improves student learning outcomes in social studies learning in elementary school. The writing in this study uses qualitative research methods, as well as a descriptive approach, in the discussion citing the results of a literature study. Furthermore, based on several sources from scientific articles, books, and relevant journals based on the results of previous studies that are in line with the topic of discussion. The results of this study, it was found that the use of video media has an influence on the learning outcomes of elementary school students, especially in social studies subjects. The use of video media in social studies learning in elementary school is valid because students who learn social studies material using video media trigger students to be more active in asking questions. discuss, and answer about the material being studied. This is because the video shows are quite interesting so that students pay attention to the material and do not get bored easily so that they can improve their learning outcomes. In the application of video media in social studies subjects, it has a considerable impact on the achievement and learning interest of elementary school students.